Increasing incidence and burden of obstructive sleep apnoea in the Finnish population: A cohort study from 2005 to 2019 - Peuranheimo, Peik; Kreivi, Hanna-Riikka; Ollgren, Jukka; Strausz, Satu; Vasankari, Tuula; Ruoranen, Toni; Ollila, Hanna M.; Hillamaa, Anne; Toppila-Salmi, Sanna; Mattila, Tiina (Elsevier BV, 2025)
Background: Obstructive sleep apnoea (OSA) is a significant public health problem. We sought to characterize the typical features of patients with OSA and to study the burden and treatment of OSA in Finland from 2005 to 2019.
Methods: Our data included adult patients with OSA (n = 50 317) treated in 2005–2019 in secondary care in the Hospital District of Helsinki and Uusimaa (HUS). We collected diagnosis and procedure codes and healthcare contacts from HUS data lake. Word search from patient records included body mass index (BMI), smoking status, Epworth Sleepiness scale (ESS), apnoea-hypopnea-index (AHI), continuous positive airway pressure (CPAP) treatment, and Mallampati score. ResMed Airview program was used to calculate the prevalence of CPAP treatment in 2018–2022.
Findings: The annual incidence of OSA increased from 99 per 100 000 to 564 per 100 000 (+470 %) during 2005–2019. The most significant increase in healthcare contacts occurred in remote care and nurse visits from 336 to 35 959 per year (+10 602 %) and from 1051 to 23 609 per year (+2146 %), respectively. The prevalence of CPAP treatment increased from 0⋅74 % to 2⋅48 % during 2018–2022 (+235 %).
Interpretation: As the prevalence of OSA is increasing, the need for more efficient treatment protocols was seen as a shift towards telemedicine and as an increase in nurse visits. Data lake offers an efficient way to analyse large data sets of OSA patient characteristics and treatment strategies.